Analisis Faktor-Faktor Yang Mempengaruhi Wewenang DPRD Dalam Pembentukan Peraturan Daerah - Rahmat, Rahmat; Dwi Cahyono, Leo; Selvi Silvana; Sepriani, Soleha; Adinda, Maulidia; Wulandhani Lisyam, Shafitri (STAI Bumi Silampari, 2026)
This study aims to analyze the factors influencing the authority of Regional House of Representatives (DPRD) in the formation of Regional Regulations (Perda). The research employed a descriptive qualitative approach using data collection through interviews and literature studies. The findings indicate that DPRD authority in forming Perda is influenced by several factors, including legal basis and formal procedures, legislative planning through the Regional Regulation Formation Program (Propemperda), coordination between DPRD and the Regional Government, and the dynamics and urgency of regional needs. These factors are interconnected and determine the effectiveness of DPRD in discussing and approving draft regional regulations. This study provides an in-depth understanding of DPRD’s role as a legislative body with collective authority in policymaking at the regional level. Furthermore, it offers recommendations for strengthening institutional capacity and legislative procedures to ensure that the resulting regulations are of high quality and aligned with the needs of the local community.